PERTUMBUHAN STEK KOPI ROBUSTA (Coffea canephora) DENGAN PEMBERIAN EKSTRAK BAWANG MERAH - Yulistiati Nengsih; Aditya Deska Wahyu (Universitas Batanghari, 2021)
Indonesia is one of the largest coffee producing and exporting countries in the world. Most of the production is robusta variety. Coffee is the fourth largest foreign exchange earner for Indonesia after palm oil, rubber and cocoa and is a source of income for the community. Coffee can be developed in a generative (seed) and vegetative way, including using cuttings. Efforts to accelerate the formation of roots in cuttings can be done by using natural growth regulators, one of which is shallots which contain auxins. The purpose of this study was to examine the effect of shallot extract on the growth of robusta coffee cuttings (Coffea canephora). This research was conducted from December 2019 to February 2020 at Campus II, Batanghari University (Pijoan). The design used in this study was a completely randomized design (CRD) with one treatment factor, namely shallot extract including; .k0 (without giving onion extract), k1 (250 g of shallots in 1 liter of distilled water), k2 (500 g of shallots in 1 liter of distilled water), k3 (750 g of shallots in 1 liter of distilled water), and k4 (1000 g of shallots in 1 liter of distilled water). Each stage of the experiment was repeated 3 times, so that there were 15 experimental plots, for each experiment there were 10 cuttings with a total of 150 cuttings. The observed data were analyzed using analysis of variance followed by the DNMRT test at α 5%. From the immersion treatment in 750 g of shallot extract in 1 liter of distilled water (k3), there was an increase in the percentage of live cuttings 47.37%, the percentage of shoots and roots growth of 83.51%, 106.06% of shoot length, and 98.03% of roots. , and the root dry weight of 225.27% compared without giving onion extract (k0).